2017
DOI: 10.4103/ijo.ijo_1023_17
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric cataract

Abstract: Pediatric cataract is a leading cause of childhood blindness. Untreated cataracts in children lead to tremendous social, economical, and emotional burden to the child, family, and society. Blindness related to pediatric cataract can be treated with early identification and appropriate management. Most cases are diagnosed on routine screening whereas some may be diagnosed after the parents have noticed leukocoria or strabismus. Etiology of pediatric cataract is varied and diagnosis of specific etiology aids in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 82 publications
(81 reference statements)
0
70
0
2
Order By: Relevance
“…The anesthetics used in pediatric ophthalmic surgery can meet the requirements of fast effect, stable effect, quick awakening, easy adjustment, small stimulation and low incidence of complications [35, 36]. Although sevoflurane is the most commonly used inhaled anesthetic in pediatric anesthesia and it has incomparable advantages over other anesthetic in the induction period of pediatric surgical anesthesia, sevoflurane alone can lead to high risk of EA.…”
Section: Discussionmentioning
confidence: 99%
“…The anesthetics used in pediatric ophthalmic surgery can meet the requirements of fast effect, stable effect, quick awakening, easy adjustment, small stimulation and low incidence of complications [35, 36]. Although sevoflurane is the most commonly used inhaled anesthetic in pediatric anesthesia and it has incomparable advantages over other anesthetic in the induction period of pediatric surgical anesthesia, sevoflurane alone can lead to high risk of EA.…”
Section: Discussionmentioning
confidence: 99%
“…Most ophthalmologic emphasis of T1D has been stressed on the influence of retinopathy [ 2 , 28 ], and the lesser known is the complication of cataract, which has resulted in more than half of the blindness worldwide [ 12 ]. Untreated cataracts in children cast tremendous burden to the child and family [ 29 ]. Our study revealed that T1D patients certainly had a higher risk of developing cataracts than nondiabetic population.…”
Section: Discussionmentioning
confidence: 99%
“…In young cataract patients, treatment options are more debated and require further consideration. It is known that the critical period of eye development ranges from 2 to 6 months of age, and emmetropization is generally achieved by 9 years of age [ 15 ]. To avoid amblyopia, some ophthalmologists recommend early surgical intervention for pediatric ocular traumatic cataracts, and in simple PCC cases without corneal or retinal injury, cataract extraction with intraocular lens implantation can restore excellent visual acuity [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%